Kalimat Interogatif Dialek Gyeongsang dalam Reply 1997 - Carlissa, Adinda Noviana; Adnyana, Putu Pramania (UI Scholars Hub, 2022)
The Gyeongsang dialect is phonologically and morphologically unique, yet current research generally focuses only on its prosody characteristics. Research related to language style and sentence-final ending in the Gyeongsang dialect has received less attention. Therefore, this study focuses on sentence-final ending or jeongyeol eomi in Korean interrogative sentences to fill the research gap. This research is qualitative research with a descriptive analysis method. Data is collected from the Korean drama Reply 1997 from the first three episodes. The result shows that a closed-ended interrogative sentence is the type of interrogative sentence most commonly used in the data, while the most widely used language style is plain style (haerache). The use of question words in an interrogative sentence in the Gyeongsang dialect also determines the variation of sentence-final ending used. The sentence-final ending ended in [o] sound, such as -go, -no, must be used for an open-ended interrogative sentence with question words. Sentence final ending ended in [a] sound, such as -ga, -na, must be used for a close-ended interrogative sentence with no question words.